Effects of organic additives on the impurity and grain structure of electrodeposited cobalt. (1st February 2021) - Hu, Y.; Deb, S.; Li, D.; Huang, Q.
Abstract: Co films were electrodeposited with different additives including dimethylglyoxime, sodium chloride, and mercapto-propanesulfonate (MPS). A systematic study was conducted using scanning electron microscope, four-point probe, secondary ion mass spectrum, and X-ray diffraction to understand the effects of such additives on the morphology, resistivity, impurity incorporation, and grain structure of film, as well as how thermal annealing influences these attributes. The addition of MPS into the electrolyte was found to significantly increase the S incorporation level and decrease the grain size, both contributing to a higher sheet resistance of film. Transmission electron microscope with energy dispersive X-ray spectroscopy and local electrode atom probe tomography were used to determine the distribution of different impurity elements. A pronounced grain structure change from columnar grains to pseudo-spherical grains was observed upon the addition of MPS in electrolyte or the incorporation of S in film. In addition to the precipitation of sporadic S-rich clusters, S and C were also found to segregate at the grain boundaries in annealed Co films, both of which are believed to correlate to the grain growth and a significant resistance drop upon annealing.